My future self: Young children’s ability to anticipate and explain future states - Atance, Cristina M. (2005)
Two experiments examine preschool-aged children’s ability to anticipate physiological states of the self. One hundred and eight 3-, 4-, and 5-year-olds were presented with stories and pictorial scenes designed to evoke thought about future states such as thirst, cold, and hunger. They were asked to imagine themselves in these scenarios and to choose one item from a set of three that they would need. Only one of the items could be used to address the future state. In both experiments, developmental differences were obtained for correct item choices and types of verbal explanations. In Experiment 2, the performance of the 3- and 4-year-olds was negatively affected by introducing items that were semantically associated with the scenarios but did not address the future state, whereas the 5-year-olds’ performance was not. Results are discussed with respect to children’s understanding of the future, theory of mind, and inhibitory control skills.